MINAT BELI KONSUMEN TERHADAP MOTOR BEAT MEREK HONDA PADA DEALER HONDA MUTIARA TIMOR STAR KUPANG - Ganggas, Fransiskus (Program Studi Manajemen dan Magister Manajemen, Fakultas Ekonomika dan Bisnis, Universitas Katolik Widya Mandira, 2023)
This research was conducted to determine the influence of cultural, social, personal, and psychology factors on consumer interest in buying Honda Beat Motor products either partially or simultaneously. The variables used consist of Culture (X1), Social (X2), Personal (X3), Psychology (X4), and Purchase Intention (Y). The data used is primary data (ordinal data). Data analysis uses parametric statistics (multiple linear regression) after the data is declared valid and reliable and meets the classical assumptions. Based on data analysis, the following research results were obtained: (1) The partial results of hypothesis testing showed that cultural, social, and personal factors did not have a significant effect on consumer buying interest, while psychological factors had a significant effect on consumer buying interest; (2) The results of simultaneous hypothesis testing show that cultural, social, personal and psychological factors have a significant effect on consumer buying interest with a magnitude of 0.763, which means that the proportion of variation in consumer buying interest is to buy Honda Beat Motor products at Honda Mutiara Timor dealers. Star Kupang is explained by cultural, social, personal and psychological factors simultaneously at 76.30% while the other 23.70% is explained by other factors outside the regression model which were not detected in this study. It can be suggested to the management of the Mutiara Timor Star Kupang Honda Dealer that: (1) it is necessary to improve quality service, continuous promotion of potential market segments in order to foster a good view of consumers to provide suggestions, positive perceptions about the existence of Honda Beat motor products to potential consumers; (2) Psychological variables are variables that affect consumer buying interest, so it is necessary to improve the product image of Honda Beat motorbikes to shape consumer motivation, perception, learning, beliefs and attitudes.